The Role of Immigration and Employment Law as a Media for Licensing and Supervision of Foreign Workers in the Republic of Indonesia - Livia Naila Elsarinda; Olyvia Sindiawaty; Ferdi Anzas Pratama (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
Today, society is being heralded by the entry of foreign workers into Indonesia which will later rob domestic jobs. If we have understood and mastered the discussion material regarding the convention; then the direction of international law is clear as a complement to enforce the law that applies to foreign workers in terms of immigration. ASEAN and ACFTA are a concrete example of the involvement of foreign workers in a place. For this reason, an understanding of international law is needed; how an agreement applies and what is contained in the agreement. Immigration, employment and international law are interrelated. They cannot stand alone. These three things will form a new order as well as how the role of immigration and manpower law in explaining how foreign workers should be employed.